Pilgrimages in the secular age : - Ryōsuke, Okamoto (Japan Publishing Industry Foundation for Culture, 2019)
The book explores the Santiago pilgrimage in Spain; the eighty-eight temple pilgrimage in Shikoku, Japan; B-grade tourist spots; so-called “power spots”; sacred anime sites; and much more. Through examining these places and the people who visit them, the reader will experience a shift in perspective and discover that in this secular age, holy places are no longer supported by religions and doctrines alone. The interchanges between a place and its community of people are what make a place holy. People are placing more importance on the shared image and experience expected to be had there.